Tracing the origin of petroleum using asphaltene carbon isotope ratios: Case study from the Songliao Basin, NE China. (3rd March 2020) - Cao, Huairen; Zou, Yan-Rong; Peng, Ping'an
Abstract: Type I and II kerogens, isolated from outcrop shales in the Songliao Basin, were performed a programed sealed-heating kinetic process. Both carbon isotope values of pyrolysis-residual kerogens and those of asphaltene extractions present gradual enrichments dependence on increasing Easy %Ro and biomarker maturity ratios. The carbon isotope (δ 13 C) values are used for the first time to analyze a close relationship between these kerogens and asphaltenes at the same level of thermal maturation, and identification oil–source rock correlation studies in theory. Such validity of the model was further tested by δ 13 C of asphaltenes and biomarker ratios in crude oils.